Arctic Norway in the Russian fin-de-siècle imagination: Evgeni Lvov-Kochetov’s travelogue Out in the Arctic Sea (1895) - Klapuri, Tintti (Association Norden, 2020)
Dans cet article, j’analyse la perception de la Norvège arctique dans l’imaginaire russe au tournant du siècle dans un cas exemplaire, le récit de voyage Po Studenomu moriu. Poezdka na sever (Autour de la mer glaciale. Voyage dans le Nord, 1895) publié par l’écrivain-journaliste Evgeni Lvov-Kotchetov. Le livre relate l’expédition dans la Russie et la Norvège septentrionales dirigée par le ministre des Finances Serge Witte. Il montre à quel point l’entourage de Witte perçoit la Norvège arctique et le Finnmark en particulier comme une partie intégrale de l’Europe en termes culturels et sociétaux. Pour eux, il s’agit un trait distinctif par rapport à la région de Murman que le récit de voyage représente telle l’arrière-cour de la Russie impériale. Dans la narration, la Norvège arctique est perçue la plupart du temps comme un modèle positif à suivre dans la modernisation du nord de la Russie, bien que certains aspects comme le tourisme de masse soient aussi considérés avec scepticisme. In this article, I discuss the ways in which Arctic Norway was perceived in the Russian imagination at the turn of the twentieth century in light of one representative example, the travelogue Po Studenomu moriu. Poezdka na sever (Out in the Arctic Sea. A Journey to the North, 1895), written by journalist-writer Evgeni Lvov-Kochetov. This travelogue describes Minister of Finance Sergei Witte’s expedition to the Russian Far North and Northern Norway in 1894. In Lvov-Kochetov’s description, the participants of Witte’s entourage view Arctic Norway, Finnmark in particular, as an integral part of Europe both in cultural and societal terms. In their view, this is what distinguishes Finnmark from the neighbouring Russian North, the Murman area, which in the travelogue is represented as the backyard of the Russian Empire. In the narration, Arctic Norway is in the main seen as a positive model for the future economic modernisation of the Russian North, even if some dimensions of modernisation, such as the development of mass tourism, are ...